Selective detection of cytochrome C by microchip electrophoresis based on an aptamer strategy. Issue 9 (8th February 2019) - Zhu, Luqi; Luo, Feifei; Li, Zhi; Dai, Ge; He, Pingang; Wang, Qingjiang; Chen, Qiming
Abstract: The release of cytochrome C (Cyt C ) plays an important role in apoptosis. In this study, selective and sensitive detection of Cyt C based on an aptamer strategy coupled with MCE was developed. Following the binding of a specific aptamer to Cyt C, the aptamer exhibited an irregular state, reducing the binding affinity of a fluorescent probe, and thus preventing the aptamer‐Cyt C complexes from detection within the MCE. The height of the detection peak of the residual aptamer linearly decreased, and therefore, the difference in peak height of residual aptamer compared to that of the initial aptamer was used to quantify the captured protein concentration. Experimental conditions such as incubation time, pH, temperature, and ionic strength were optimized. A measurement of Cyt C concentration by MCE was achieved within 135 s, with a limit of detection as low as 0.4 nM. The proposed method has high selectivity and good stability for the detection of Cyt C . The experimental results demonstrate that this method is quick, consumes only a small quantity of sample, is highly selectivity and exhibits high sensitivity.